The effectiveness of prenatal breastfeeding education and postnatal breastfeeding support among primiparous mothers in Hospital Universiti Sains Malaysia - Fauzi, Rosuzeita (2016)
Background: In Malaysia, the rates of mothers who are breastfeeding exclusively remain low, even though the World Health Organization had recommended the mother to breastfeed their infants exclusively for the first six months of age. The government hopes and expects that the percentage of exclusive breastfeeding practice among babies six months of age will increase to 30% by 2015. Objective: To determine the effectiveness of prenatal breastfeeding education and postnatal breastfeeding support in improving breastfeeding outcomes. Method: A quasiexperimental design was used to test the effects of intervention on breastfeeding confidence, exclusivity and duration. A purposive sample of 96 primigravida mothers (intervention group (IG) =48, control group (CG) =48) had been recruited from the Obstetrics and Gynaecology clinic and antenatal ward at Hospital USM. Data were collected using the Breastfeeding Self-Efficacy Scale-Short Form (BSES-SF) and the Breastfeeding Assessment Questionnaire. Mothers in the IG received current usual care and two hours of additional education programme on breastfeeding (lecture, educational video, demonstration, practical and discussion) in a small group, breastfeeding booklet, note from the module, and received postnatal breastfeeding support in the first week of postpartum. Mothers in CG received the current usual care only. The mothers were assessed at the first and sixth week and then the fourth and sixth month of postpartum. Results: Mothers in the IG had greater breastfeeding self-efficacy score (M= 57.19, SD= 6.49) at the first week of postpartum than mothers in the CG (M= 53.85, SD= 7.50), p= 0.023. A greater percentage of mothers in the IG were practicing full breastfeeding compared to the CG at all of the follow up weeks: 1 week (77.1% vs. 60.9%), 6 weeks (53.2% vs. 42.2%), 4 months (54.3% vs. 29.5%) and 6 months (27.3% vs. 16.7%) postpartum respectively. The results indicated that there was a statistically significant difference between the groups at the fourth month postpartum (X2=5.671, p= 0.017). The results indicated that the continuation of breastfeeding rates of the IG were higher than those of the CG at all four follow-up periods. However, the results showed only two follow up weeks that were significant (week 6, X2=5.414, p= 0.020, month 4, X2=7.515, p= 0.006). The mean duration of breastfeeding in the IG was 20.8 weeks compared to 17.0 weeks in the CG. Conclusions: Prenatal breastfeeding education and postnatal support can effectively increase breastfeeding confidence, duration and exclusivity outcomes among primiparous mothers.